1988
DOI: 10.1007/bf01044385
|View full text |Cite
|
Sign up to set email alerts
|

Convicted but innocent: Wrongful conviction and the criminal justice system.

Abstract: Legal literature from the beginning of the century, as well as more recent studies, furnish us with accounts of cases of innocent men and women who were tried and convicted of serious crimes throughout the United States. This study surveys the literature on those cases and describes these wrongful convictions by the distribution of offenses, of sentences, of actual punishment inflicted, and types of error contributing to the wrongful conviction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
67
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(67 citation statements)
references
References 3 publications
0
67
0
Order By: Relevance
“…Huff, 1987;Rattner, 1988). In 1998, Wells et al reported on 40 cases in the United States involving men who were wrongfully convicted of sexual assaults, and who were later exonerated by DNA evidence.…”
mentioning
confidence: 99%
“…Huff, 1987;Rattner, 1988). In 1998, Wells et al reported on 40 cases in the United States involving men who were wrongfully convicted of sexual assaults, and who were later exonerated by DNA evidence.…”
mentioning
confidence: 99%
“…False identi®cation is the single major source of wrongful convictions (Levi, 1997;Rattner, 1988;Wells, 1997). It is dicult to discriminate accurate from inaccurate identi®cations by listening to testimony (e.g.…”
Section: Researchmentioning
confidence: 99%
“…One can understand why so many cases of wrongful conviction have been discovered (Brandon and Davies, 1973;Rattner, 1988), despite the odds against discovering wrongful convictions. The police do not usually search for further evidence on a crime for which a defendant has already been convicted.…”
mentioning
confidence: 96%